The secret of the London contract from 1915 - Nadoveza Branko I. (Baština, 2022)
The Treaty of London of April 1915 was primarily provided for an expansion of Italy and its access to the Entente and a break with the Central Powers. The Treaty of London did not mention the creation of a "Greater Serbia", but what Italy will gain and what will remain for Serbia and Yugoslavian peoples within Austria-Hungary. Bulgaria and its compensations in Macedonia are especially included in that agreement, to the detriment of Serbia. The Treaty of London was secret and was therefore rejected in Versailles. Its ideas were only partially realized. It was an important military, political and moral issue. The ideas of the Treaty of London were a subject of speculation.